Fourier Transform Infrared Analysis of Urinary Calculi and Metabolic Studies in a Group of Sicilian Children (Iranian Journal of Kidney Diseases, 2017)
Introduction. Prevalence of urinary calculi in children has been increasing in the past years. We performed an analysis of the chemical composition of stones formers of the pediatric population in our geographical area over the years 2005 to 2013. Materials and Methods. Fourier transform infrared spectroscopy was employed for the determination of the calculus composition of a group of Sicilian children, and metabolic studies were performed to formulate the correct diagnosis and establish therapy. Results. The prevalence of stone formation was much higher for boys than for girls, with a sex ratio of 1.9:1. The single most frequent component was found to be calcium oxalate monohydrate, and calcium oxalates (pure or mixed calculi) were the overall most frequent components. Calcium phosphates ranked 2nd for frequency, most often in mixed calculi, while urates ranked 3rd. The metabolic disorder most often associated with pure calcium oxalate monohydrate calculi was hypocitraturia, while hyperoxaluria was predominantly associated with calcium oxalate dihydrate calculi. Conclusions. Mixed calculi had the highest prevalence in our pediatric population. Our data showed that Fourier transform infrared spectroscopy was a useful tool for the determination of the calculi composition.